Jacqueline Kelen: Ženy z Bible.; Ann Belford Ulanov: Pramatky Ježíše Krista.: Books, Brno 1999; One Woman Press, Praha 2003 - Knotková-Čapková, Blanka (Lidé města, 2004)
A review of the books by Jacqueline Kelen and Ann Belford Ulanov.